Activation of the Unreactive Bond in C70 Fullerene toward Diels‐Alder Reaction by Encapsulation of a Lithium Atom. Issue 19 (3rd September 2020) - Li, Zisheng; Jiang, Yuhang; Wu, Yabei; Wang, Zhiyong
Abstract: Diels‐Alder cycloaddition reaction is useful for generation of covalent derivatives of fullerenes. Diels‐Alder reactions of C70 and dienes usually take place at the carbon‐carbon bond that has a short bond length in C70, while the bonds with long lengths are generally unreactive. In this paper, we investigated the reactivities of Li + @C70 and Li@C70 toward Diels‐Alder reactions with cyclohexadiene by means of density functional theory calculations. We found that the thermodynamic and kinetic reactivities of the fullerene cage are changed significantly after the encapsulation of the lithium ion or atom. The encapsulated lithium ion causes a remarkable decrease of the activation barrier for the cycloaddition reaction, which can be ascribed to the enhanced orbital interaction between cyclohexadiene and the fullerene cage. The unreactive bond with a long length in C70 is activated efficiently after the encapsulation of the lithium atom. According to the activation‐strain model analysis, the improved reactivity of the long bond is associated with the small deformation energy and large interaction energy of the reactants. Unlike conventional Diels‐Alder reactions that proceed through concerted mechanism, the reaction of Li@C70 and cyclohexadiene undergoes an unusual stepwise mechanism because of the open‐shell electronic structure of Li@C70 . Abstract : Encapsulation of a lithium atom in C70 efficiently activates the unreactive bond of the fullerene cage toward Diels‐Alder reaction with cyclohexadiene. Because of the distribution of excess unpaired spin in Li@C70, the cycloaddition reaction takes place through a stepwise mechanism instead of the conventional concerted mechanism.